Hubungan Aktivitas Fisik dan Indeks Massa Tubuh (IMT) dengan Siklus Menstruasi pada Remaja Putri di Desa Balangtaroang Kabupaten Bulukumba - Eka Suprapti; Vivi Adriana; Maria Kurnyata R.K; Yuliana Yusfira (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2022)
Background: Menstrual cycle disorders that are not treated promptly and properly will result in various health problems. The purpose of this study was to determine the correlation of physical activity and body mass index with the menstrual cycle of young girls in Balangtaroang village, Bulukumba Regency Methods: The sampling method used in this study is non-probability sampling with a total sampling technique of 25 respondents. The test used in this research is the Somers'd statistical test. Results: Where the results of the research for the variable physical activity on the menstrual cycle based on the Somers'd test results obtained p value = 0.044 <? = 0.05 and an average value of 2.120, this means that H0 is rejected and Ha is accepted, and for the body mass index variable on the menstrual cycle based on the Somers'd test results, p value = 0.133> ? = 0.05 and an average value of 1,400 Conclusion: Based on the results of the research above, it can be concluded that there is a correlation between physical activity and the degree of the menstrual cycle and there is no correlation between body mass index and the menstrual cycle.